Astrocytes and their potential role in anti-NMDA receptor encephalitis. (June 2020) - Ismail, Fatme Seval; Faustmann, Pedro M.
Abstract: The N-methyl-d -aspartate receptor (NMDAR) encephalitis is the most common form of autoimmune encephalitis. Antibodies against the GluN1 subunit of the NMDAR showed in primary cultures of rat hippocampal neurons and in a mouse model pathogenic effects including cross-linking and internalization of the target receptors (NMDAR). Several studies demonstrated that not only neurons, but also astrocytes express functional NMDA receptors including GluN1 subunit. It is conceivable that the pathogenic antibodies against the NMDAR causing the anti-NMDAR encephalitis affect not only the neuronal receptors, but also the NMDAR on astrocytes. We hypothesize that antibodies against NMDAR can lead to cross-linking and internalization of the target receptors in astrocytes similar to neurons with disruption of the calcium release within the astrocytes and consequently blocking release of inhibitory gliotransmitters. Further, we assume influence on expression of aquaporin 4 channels and gap-junctional communication due to modification of the astrocytic NMDAR. The disruption of these interactions and dysbalance could result in impairment of CNS homeostasis and co-determine the severity of clinical disease manisfestation and recovery.